Self-reliance and self-control in adolescents with Inflammatory Bowel Disease in connection with the necessity to change a gastroenterologist after reaching the age of maturity - Wardak, Katarzyna; Celińska-Cedro, Danuta; Nagórska, Małgorzata (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Inflammatory bowel disease (IBD) is among five most frequent gastrointestinal diseases and is the most common chronic disease of the gastrointestinal tract in children. Although children due to the early diagnosis will suffer the longest and the most acute, they may lead a life similar to their healthy peers. The aim of the study was to investigate the degree of selfcontrol in adolescents with IBD in connection with the necessity of the transition to the care of gastroenterology clinic for adults at the age of 18. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The survey was conducted among young people aged 15 to 18 diagnosed with IBD, the patients of Gastroenterological Clinics in Warsaw and Rzeszow. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Ulcerative colitis was diagnosed in 50.67% of the children while Crohn’s disease was found in 42.67%. The average age of the onset was approx. 12.13 ± 3.82 among the children. More than a half of the respondents assessed the range of possessed information about the disease entity as rather sufficient. Vast majority of young people in the overall study population could formulate their observations and concerns regarding the treatment independently. Over 90% of patients in the study declared knowing the names and doses of medicines, however, in one fifth of the subjects the regularity of their administration was still supervised by parents. All respondents were accompanied by parents during a visit at a specialist. More than a half of the respondents would not be able to contact a specialist alone if necessary. The subject of hazardous behaviour (smoking, drinking, drugs) and sexual intercourse was not discussed during the visits. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. 1. Adolescents knew the essence of the disease, but were engaged in the process of self-control only to a limited extend. 2. Nonmedical issues like lifestyle, fertility, professional development were not discussed in the gastroenterological clinics for children.